Regional strategies in Baltic countries - Agita Slara (European Regional Science Association (ERSA), 2003)
The article describes existing situation and gives analysis of the regional development policy determination and implementation in the all three Baltic countries. The starting point of the regional policy formulation and creation was equal for Estonia, Latvia and Lithuania since 1991. According statistical indicators there are differences between implementation of the regional development activities between all Baltic countries and in regions of inside each country. Disparities between countries illustrate Gross domestic product per capita according to purchasing power standards in 2000 were: Latvia 6700, Lithuania 7500 and Estonia 8600 PPS. Registered unemployment rate, which is one of the statistical indicators for the regional development evaluation, shows negative regional disparities in Latvia in 2001. The highest difference was between Riga region (the richest) and Latgale (the poorest) region is 3.7 times. The author is analysed more detail differences between regions in Latvia and main guidelines of the regional policy implementation in Lithuania and Estonia. Analyses show differences of the institutional mechanism in all three Baltic Countries. The legal bases are different by time and content in Estonia, Latvia and Lithuania. The executive institutions are different at national and regional levels in all three Baltic Countries. In Latvia are accepted five regions correspond to EU NUTS level 3. In Estonia are five regions and in Lithuania 10 counties correspond to regions. Regional development policy support is concentrated on separate territories in each country according EU regional policy principles. The most important regional development program is specially supported region program, which is on-going regional development instrument in Latvia. The main part of specially supported areas is located in Latgale region. National Government of Latvia was selected Latgale and Zemgale regions as the target regions for Phare 2000 support. In 2001-2003 National Policy for Regional Development in Lithuania are focused on three target regions for concentration of Phare support and Lithuania Cabinet support to the regional development: Klaipeda-Taurage, Marijampole and Utenas counties. In Estonia the regional policy to target areas is implemented through the regional development programs as Program for the Agricultural areas, Program for the Industrial areas, Program for the Islands, Program for the Network of centres, Program for the Local Initiative, Program for the cross-border-Cooperation and Program for the Setomaa region. The expected results and evaluation system are not included in the regional development policy documents in all three countries. It is one of the weakest points of the regional development policy implementation process in Latvia. The regional development legislation is very general without monitoring indicators and evaluation process. The author has analysed prepared development strategies of regions according possibility to evaluate success of development planning documents. The descriptive analyse of documents, statistical indicators, matrixes and interviews with responsible persons for the regional development policy at national level and regional level were used in the research.
Keywords: 330